Synthesis and Adsorbent Performance of Modified Biochar with Ag/MgO Nanocomposites for Heat Storage Application - R. Venkatesh; N. Karthi; N. Kawin; T. Prakash; C. Ramesh Kannan; M. Karthigairajan; Ketema Bobe (Adsorption Science & Technology)
Heat storage is a major problem in the world. Many research is going on the heat storage application. This research investigates the novel Ag/MgO/biochar nanocomposites for heat storage. Ag/MgO/biochar nanocomposites were fabricated using solvent-free ball milling techniques. According to several analytical measurements, the Ag/MgO nanoparticles in biochar are uniformly dispersed across the carbon interface. This type of adsorbent material has been characterized by different techniques such as X-ray diffraction pattern analysis (XRD), FTIR analysis, scanning electron microscope (SEM), and transmission electron microscope (TEM) as all indicate the surface morphology and successful ball milling synthesis of Ag/MgO nanocomposites. The UV visible spectroscopy wavelength range of AgNPs and MgONPs is 330 nm and 470 nm, respectively. FTIR analysis revealed that different functional groups of modified biochar nanocomposites such as O-H group are 3728 cm-1 and for C-H bond is 932 cm-1, C-O group is 1420 cm-1, and C=O is 1785 cm-1, respectively. Adsorption tests showed that 1.0 gL-1 dosage with 60% phosphate removal, an ion, and 0.2 gL-1 of dosages that had 85% methylene blue decomposition, a charged synthetic dye, were the lowest absorption levels. This research suggests that ball milling offers the advantages of stabilization and chemical adaptability for customized remediation of different atmospheric contaminants. Ball milling is a facile and feasible process to fabricate carbon-metal-oxide nanomaterials.